Melatonin decreases oxidative stress in Drosophila melanogaster exposed to manganese - Medina-Leendertz, Shirley; Mora, Marylú; Vielma, , José Ramón; Bravo, Yanauri; Atencio-Bracho, Lorena; Leal-Yépez, Alejandra; Arcaya, José Luis; Bonilla, Ernesto (Investigación Clínica, 2018)
Abstract. In a previous study we found that manganese induces a prooxidant effect on Drosophila melanogaster. In the present study the effect of melatonin (MEL; 0.43 mM) in oxidative stress markers of D. melanogaster after manganese (Mn; 30 mM) intoxication was determined after 6 days of treatment. Three groups were used: 1. Mn (exposed to Mn); 2. Control (maintained in standard medium); 3. MEL 6 d (treated with MEL). In four additional groups, the effect of MEL treatment for 40 days after the intoxication was determined: a. Mn-Control (exposed to Mn and no additional treatment for 40 days); b. Mn-MEL (exposed to Mn and treated with MEL for 40 days); c. Control 40 d (maintained in standard medium for 40 days); d. MEL 40 d (treated with MEL for 40 days). After 6 days, an increase in the concentrations of H , NO•, MDA, protein carbonyl and 8-OHdG, and the activities of SOD, CAT, NOS and GSH-Px was observed in Mn intoxicated flies. A decrease of GSH was also detected. At 40 days, in the Mn-Control group, the increase in the concentrations of H 2 protein carbonyl and 8-OHdG and in the activities of GSH-Px, CAT and SOD was maintained. In contrast, the concentration of GSH and MDA was decreased. Similarly the concentrations of H 2 O , NO•, GSH and the activities of SOD, CAT, GSH-Px and NOS were decreased in the Mn-MEL group compared to the MnControl. In conclusion, the prolonged treatment with MEL mitigated the oxidative stress in D. melanogaster after exposure to Mn. 2 O 2 2 O 2,